Pengembangan Media Berbasis Kearifan Lokal Pada Materi Menggali Pengetahuan Baru Dari Teks Nonfiksi Siswa Kelas IV SDN Mangundikaran 2 - Faradina Damayanti Susanto; Rian Damariswara; Erwin Putera Permana (Departement of Mathematics Education, 2023)
This research is motivated by the problems that exist at SDN Mangundikaran 2, which show Indonesian language learning in the basic competencies of non-fiction texts in grade IV. This research is motivated by the problems that exist at SDN Mangundikaran 2, which show Indonesian language learning in the basic competencies of non-fiction texts in grade IV. In this study using the RnD (Research and Development) method. The development model used is the ADDIE research model which has 5 stages, namely: (1) Analysis Stage, (2) Design Stage, (3) Development Stage (4) Implementation Stage (5) ) Evaluation Stage (Evaluation). The subjects of this study were 30 students in grade IV at SDN Mangundikaran 2 Nganjuk Regency. The data analysis technique used is descriptive qualitative analysis and quantitative descriptive analysis. The results of this study indicate that (1) the validation results obtained from the media validator reach a percentage of 88% and the material validator reaches a percentage of 84%. Then the results of the validity of the Pataya media development obtained an average percentage of 86%. So that the development of pataya media can be declared valid. (2) The results of the teacher's response questionnaire reached a percentage of 85% and the results of the student response questionnaire reached a percentage of 81%. Then the practicality of the pataya media obtained an average percentage of 86%. So that media development is declared practical. (3) The results of the analysis of evaluation questions (post-test) obtained an average percentage of 84%. So that the development of pataya media is declared effective for use.